Studi Kelayakan Bisnis UMKM Pabrik Tahu Rizky di Desa Sruwen - Ray Alha Latahza Sakti Jo; Novitasari, Rini; Citra Fahmi Nugrahani; Mokhammad Khukaim Barkhowa (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The Rizky Tofu Factory, an SME in Sruwen Village, is a business that contributes to meeting the community’s food needs and creating jobs. However, this business still faces various challenges, such as intense competition, labor shortages, and suboptimal financial management. This study aims to analyze the feasibility of the Rizky Tofu Factory business from the perspectives of finance, human resources (HR), and marketing. The study employs a mixed-methods approach, combining qualitative and quantitative methodologies. Primary data was collected through interviews and direct observation, while secondary data was obtained from various literature and supporting documents. Data analysis was conducted using qualitative descriptive methods through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that from a financial perspective, the business has a positive cash flow and is able to generate stable net profits, indicating a healthy financial condition. From the human resources perspective, the workforce effectively supports the production process through the achievement of production targets, efficient use of working time, high product quality, and a high level of discipline. From the marketing perspective, the business is supported by high-quality products, competitive pricing, easily accessible distribution channels, and effective promotion through social media and direct communication with customers. Based on the results of the analysis, Rizky Tofu Factory has been deemed viable for operation and further development. It is hoped that this study will serve as a basis for business owners to enhance their competitiveness and ensure the sustainability of their businesses